Recognising the land rights of indigenous peoples and rural communities - Williams, R (Refugee Studies Centre, University of Oxford, 2012)
Current global trends are putting increasing economic pressure on land and natural resources, raising the risk that new waves of internal displacement may be caused by the combined forces of climate change and large-scale investment in agriculture.